Effects of 5-azacytidine-2’- deoxycytidine on the proliferation, cell cycle, and apoptosis of fetal bovine fibroblast cells - YU Mengfei; WANG Wenlu; YI Jianming (浙江大学学报. 农业与生命科学版)
Fetal bovine fibroblast cells (FBFCs) are widely used in cellular reprogramming and methylation. In this study, the effects of 5- azacytidine-2’- deoxycytidines (5-Aza-CdR), a DNA methylation inhibitor on the physiological characteristics of FBFCs were investigated. The FBFCs derived from a bovine fetus were treated with 5-Aza-CdR at different concentrations for 24, 48 and 72 h, respectively, to determine the changes of cell proliferation, viability, cell cycle distribution and apoptosis rates. The results demonstrated that 5- Aza- CdR treatment in the FBFCs resulted in a decrease of cell proliferation, cell viability, and an increase of total cell apoptosis in a dose-dependent manner. The best treatment strategy for 5-Aza-CdR was less than 0.1 μmol/L for 24 h, which showed minimal adverse effects on FBFCs. The above results indicate that the low dose DNA demethylation inhibitor treatment in FBFCs is beneficial for cell reprogramming.